LEGISLATIVE CANDIDATE MARKETING STRATEGY FOR ATTRACT MILLENNIAL VOTER IN PEMILU 2019 : CASE STUDY INDONESIA SOLIDARITY PARTY (The Indonesian Journal of Business Administration, 2019)
The presence of a new party namely the Indonesian solidarity party, legislative candidates from the party must use a new method. increasingly critical communities such as milennials demand that they take a more persuasive approach. This research aims to study participation in pemilu with the presence of the Indonesian Solidarity Party and the identification of marketing strategies to increase millennial participation in the 2019 elections and overcome the problems discussed by Yoki Oktorian Sukardi, a legislative candidate from the Indonesian Solidarity Party.The analysis in this study uses internal and external factors to be able to provide effective and efficient solutions. Internal analysis was carried out to analyze STP (Segmenting, Targeting, Positioning) and Market Mix (4P) of Yoki Oktorian Sukardi, a legislative candidate from the Indonesian Solidarity Party. Then analyze externally using STEEPLED analysis (Sociocultural, Techonological, Economic, Environment, Political, Legal, Ethical, Demographic) in Sumedang district, competitor analysis of other party legislative candidates and millennial voter analysis in Sumedang.Based on the results of the survey that has been obtained, millennial voters in the Sumedang area choose legislative candidates based on the resolution of policy problems such as work programs and real things given to the public. In addition, the ideology and issues raised were less accepted by millennials in the Sumedang region whose majority of voters were rational and critical.solution suggested to the legislative candidates from the Indonesian Solidarity party that is conducting an effective campaign strategy and positioning evaluation by adding more popular issues in the community.Keywords:  Marketing Strategy, political marketing, Brand Awareness, Communication Strategy.